Van Neck-Odelberg disease: a rare cause of childhood limping - Ferreira,Joana (2019)
Introduction: Joint pain and limping are common in pediatric age. Assessment of a child with joint pain requires differentiating benign conditions from those requiring urgent medical attention. Case report: A previously healthy nine-year-old boy was brought to the Emergency Department with fever and pain in the left ankle and hip associated with limping. He reported fever, abdominal pain, and slightly dry cough two weeks before admission. Blood analysis revealed an elevation in erythrocyte sedimentation rate and C-reactive protein serum concentration. Serology tests were positive for Mycoplasma pneumoniae acute infection and imaging studies enabled the diagnosis of Van Neck-Odelberg disease (VND). Discussion/Conclusion: Presence of joint pain often represents a diagnostic challenge, especially in children who present with fever and elevation of acute-phase reactants. VND is a rare cause of limping and in this case corresponded to an imaging finding. The final diagnosis was reactive arthritis secondary to M. pneumoniae infection.